Option A: x^2 +3x-1 is the correct answer
Step-by-step explanation:
Given functions are:
![f(x) = x-2\\g(x) = x^2+1](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x-2%5C%5Cg%28x%29%20%3D%20x%5E2%2B1)
We have to find (f+g)(x), which is the addition of two given functions
So,
![(f+g)(x) = f(x) +g(x)\\= 3x-2 + (x^2+1)\\= 3x-2+x^2+1\\= x^2+3x-2+1\\=x^2+3x-1](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%20%3D%20f%28x%29%20%2Bg%28x%29%5C%5C%3D%203x-2%20%2B%20%28x%5E2%2B1%29%5C%5C%3D%203x-2%2Bx%5E2%2B1%5C%5C%3D%20x%5E2%2B3x-2%2B1%5C%5C%3Dx%5E2%2B3x-1)
Hence,
Option A: x^2 +3x-1 is the correct answer
Keywords: Functions, addition
Learn more about functions at:
#LearnwithBrainly
The answer is 4. -4 is the opposite of 4
3 with a little 3 in the top right corner because your are multiplying 3 times
Answer:
![y^{\frac{3}{2}](https://tex.z-dn.net/?f=y%5E%7B%5Cfrac%7B3%7D%7B2%7D)
Step-by-step explanation:
Let ![m=\sqrt{y^3}](https://tex.z-dn.net/?f=m%3D%5Csqrt%7By%5E3%7D)
![m=(y^3)^{\frac{1}{2}}\\\\m=y^{3\times \frac{1}{2}}\ \ \ \ \ \ \ \ \ [as\ (x^a)^b=x^{ab}]\\\\m=y^{\frac{3}{2}](https://tex.z-dn.net/?f=m%3D%28y%5E3%29%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%5C%5C%5C%5Cm%3Dy%5E%7B3%5Ctimes%20%5Cfrac%7B1%7D%7B2%7D%7D%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5Bas%5C%20%28x%5Ea%29%5Eb%3Dx%5E%7Bab%7D%5D%5C%5C%5C%5Cm%3Dy%5E%7B%5Cfrac%7B3%7D%7B2%7D)
Answer:
Chocolate Chips are 1.50 per pound and Walnuts are 3.25 per pound.